Resveratrol protects pancreatic beta cell and hippocampal cells from the aggregate-prone capacity of hIAPP - Carlos González-Blanco; Ángela Cristina Lockwood; Beatriz Jiménez; Sarai Iglesias-Fortes; Patricia Marqués; Gema García; Ana García-Aguilar; Manuel Benito; Carlos Guillén (Scientific Reports, 2024)
Abstract Type 2 diabetes mellitus and Alzheimer’s disease, are two closely related pathological situations that are connected at the molecular level. In recent years, amylin, which is co-secreted with insulin, has been proposed for being a main actor in this context due to its capacity to form aggregates in a β-sheet-like structure. In a diabetic milieu, there is an increase in the production and secretion of insulin and amylin. We have analysed the role of resveratrol on aggregate formation and in the production of extracellular vesicles with amylin in its interior and in pancreatic β cells overexpressing human amylin (INS1E-hIAPP). Furthermore, we have explored the consequences of the exposition of the conditioned medium derived from INS1E-hIAPP in the hippocampal cell line HT-22 and the role of resveratrol in this cell line. Hippocampal cells were exposed to conditioned media obtained from rat insulinoma 1E overexpressing human amylin in the presence or in the absence of resveratrol. When we exposed HT-22 cells to the conditioned media of INS1E-hIAPP we observed amylin-aggregates inside HT-22 cells. Resveratrol was able to alleviate this effect not only in HT-22 but also in pancreatic β cells. Furthermore, resveratrol decreased the average exosome size produced by the INS1E-hIAPP stimulated with high glucose, diminishing the toxic effect of these exosomes in HT-22 cells. We have uncovered that resveratrol inhibits the aggregation capacity of amylin and it can diminish the deleterious spreading of the toxic protein, to other cell types such as the hippocampal neuron cells, HT-22.